2010
DOI: 10.1111/j.1346-8138.2010.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple vascular eccrine spiradenomas: A case report and published work review of multiple eccrine spiradenomas

Abstract: Eccrine spiradenoma (ES) usually occurs as a solitary small nodule. It presents rarely as multifocal or multiple localized tumors arranged in a linear, zosteriform or nevoid distribution. We present a rare case of a 55-year-old woman who had a 48-year history of multiple vascular eccrine spiradenomas (VES) localized on the left side of the submandibular region and neck. All five tumors were skin-colored or pinkish-purple, and ranged in size 1.5-2.5 cm. Histologically, each tumor was composed of two characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Pathways underlying the pathogenesis of the tumor are still being elucidated. The potential role of hereditary factors was pointed out by some investigators who suggested autosomal and dominant inheritance but their observations are still not established [5]. Interestingly, trauma has been speculated as precipitating factor leading to the development of ES [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathways underlying the pathogenesis of the tumor are still being elucidated. The potential role of hereditary factors was pointed out by some investigators who suggested autosomal and dominant inheritance but their observations are still not established [5]. Interestingly, trauma has been speculated as precipitating factor leading to the development of ES [6].…”
Section: Discussionmentioning
confidence: 99%
“…Solitary ES occurs more frequently in men, whereas multiple ES appear more commonly in females, with an estimated female to male ratio of 3:1 [7]. The onset of the tumor is typically observed during the second to fourth decade of life.…”
Section: Discussionmentioning
confidence: 99%
“…7 As a remote echo of such erroneous assumptions, we find even current reports of linear naevi said to be arranged in a "zoosteriform" or "dermatomal" pattern. [30][31][32][33][34] In 1969 MacDonald and Sims, 35 being unaware of Blaschko's work, studied photographs and descriptions in several case reports and reported 16 cases in their own records stating that "no association could be found between the lesions and anatomical features of the skin." They concluded that "the epidermis is not … inherently segmental.…”
Section: Contemporary (1901) and Later Work (1941-1970) On The Linesmentioning
confidence: 99%
“…It mainly affects adults, with the highest incidence in the fourth decade of life 1 . Yoshida et al 2 divided ES into solitary and multiple ES on the basis of its clinical appearance. Most presentations of ES are solitary and show no predilection for any sex.…”
Section: Introductionmentioning
confidence: 99%